A biophysical study of gene nanocarriers formed by anionic/zwitterionic mixed lipids and pillar[5]arene polycationic macrocycles. Issue 17 (12th April 2017) - Barrán-Berdón, Ana L.; Martínez-Negro, María; García-Río, Luis; Domènech, Òscar; Tros de Ilarduya, Conchita; Aicart, Emilio; Junquera, Elena
Abstract : A multivalent cationic macrocycle is used as a mediator between plasmid DNAs and anionic lipids (ALs) to build an efficient and safe gene nanocarrier. Abstract : The use of divalent cations as mediators between anionic lipids (ALs) and nucleic acids has been explored for several years in gene therapy. However, a promising anionic lipid system which could surpass the outcomes of current cationic lipids (CLs) has not been found yet. One plausible reason for such poor efficiencies may be the impossibility of AL–DNA lipoplexes mediated by divalent cations to reach charge inversion, in contrast with the usual behavior of CL–DNA lipoplexes. In the present study, divalent bridge-cations have been replaced by a multivalent positively charged macrocycle in order to see whether charge reversal is reached and how this fact may improve transfection efficiency (TE). For that purpose, an extensive biophysical and biochemical study has been carried out on lipoplexes constituted by a mixture of: (i) an anionic lipid DOPG (sodium salt of 1, 2-dioleoyl- sn-glycero -3-phospho-(1′- rac -glycerol)); (ii) a zwitterionic lipid DOPE (1, 2-dioleoyl- sn-glycero -3-phosphatidylethanolamine), which acts as a neutral helper lipid at physiological pH 7.4; (iii) a plasmid DNA (pDNA); and (iv) a polycationic macrocycle, pillar[5]arene (P 10+ ), with the role of bridging the electrostatic interaction between the anionic mixed lipids and the pDNA, also negatively charged. The studies have been done at several DOPG molar compositions ( α ) and pillar[5]arene concentrations. Electrochemical experiments (zeta potential and gel electrophoresis) have revealed that, interestingly, DOPG/DOPE–P 10+ –pDNA lipoplexes show a charge inversion. Both studies have indicated that, at [P 10+ ] ≥ 15 μM, pDNA is efficiently compacted by DOPG/DOPE mixed lipids, using P 10+ as a bridge between the negative charge of the AL and anionic pDNA. SAXS diffractograms have shown the presence of two lyotropic liquid crystal phases: an inverted hexagonal one ( H cII) found at low composition ( α = 0.2), and a lamellar one ( L α ) at medium composition ( α = 0.5). Cryo-TEM and AFM experiments have confirmed these structures. Transfection and cell viability experiments using COS-7 cells in the presence of serum have reported moderate-to-high transfection levels and good cell viability results. The whole ensemble of the biophysical and biochemical results of the DOPG/DOPE–P 10+ –pDNA lipoplex indicates that this system may open up a novel and very promising route in the anionic non-viral gene vectors field.